Funkcjonowanie dzieci, młodzieży i dorosłych w rodzinach rozłącznych przestrzennie na skutek migracji ekonomicznych - Bakiera, Lucyna; Doiczman-Łoboda, Natasza (Człowiek i Społeczeństwo, 2018)
The main goal of the article is to take a theoretical reflection on a spatially separated family (also called temporary incomplete or transnational) as a result of labor migration. Global socio-cultural changes and the evolution of individual attitudes towards the life are changing contemporary families. Despite the transformation the family plays a key role in human development, and adults not only highly value family life and children, but perceive the child as a source of personal and family happiness. The article presents the scope of economic migration of Poles and their impact on family life. The main remarks refer to the psychological effects of separation for children, adolescents and spouses. Attention is drawn to the risk of loneliness, parentification and parental alienation. This paper presents also an attempt to classify spatially separated families as a result of economic migrations.